Tindak Tutur Direktif dalam Ungkapan Kebencian yang Dilakukan secara Anonim melalui Situs Kirim Pesan Secreto - Ilma Sarah Zena (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study aims to analyze and describe the forms and functions of directive speech acts expressed in hate speech on the Secreto message-sending site. Secreto is a site that is currently being used by several groups because it gives access to anyone to send messages anonymously (without an identity) thereby increasing the potential for hate speech through the site. The researcher used a qualitative descriptive research method by applying Yule's pragmatic theory and Searle's theory of directive speech acts. Researchers collected data on hate speech and obtained screenshots on the Secreto site, taken publicly by the respective account owners. The data were then analyzed using pragmatic analysis method, which is based on a pragmatic point of view. The result of this study indicates twenty expressions of hate speech included in the six directive speech acts, consists; 4 data of commanding, 3 data requesting, 4 data of inviting, 2 data of forbidding, 5 data of criticizing, and 2 data of advising.